FRAGMENTED HOME AND PERENNIAL MEMORY: EXPLORING DIASPORIC IDENTITY THROUGH CHRONOTOPE IN HALA ALYAN’S SALT HOUSES (CAHIERS MAGELLANES-NS, 2024)
Narratives of displacement engaged with memory help accentuate the spatio-temporal existence of an individual. The present study enquires the model of displacement and memory in Hala Alyan’s novel Salt Houses to focus on the intricate interplay of temporal and spatial dimensions of constructing diasporic identity. Alyan employs unique narrative techniques, such as unreliable narrator, intermixing of first-person perspective and memoir-like tones, to vividly portray the fragmented memories of displaced characters. These narrative choices reflect a broader historical narrative of trauma, resettlement, and the enduring impact of displacement on individual and collective identities. Alyan’s investigation is profoundly rooted in her Palestinian heritage. It brings the conflicting situations of generational shifts into limelight. The anguish and dislocation characterise the Palestinian diaspora in the novel. Alyan’s nuanced examination illuminates the complex identities of Palestinians living as part of a diaspora. The existence of the diaspora caught between the memories of their homeland and the realities of their hostland is also portrayed in the novel. Further, through the lens of Mikhail Bakhtin’s concept of chronotope, the paper investigates the intrinsic connectedness of time, space and memory. Memory, in this context, acts as an important link between the homeland and the hostland, between the past and the present. It encapsulates the experiences of displacement, adaptation and the continuous negotiation of identity. In Salt Houses, memory is not just a passive recollection of the past but an active, dynamic force that shapes the characters' lives and identities. The study explores how memory, within the framework of the chronotope, serves as a bridge that connects the historical and personal dimensions of the characters’ experiences. This exploration provides profound insights into how individuals grapple with their place within society, the weight of history, the notion of home, and the intricacies of identity. Through the examination of the above-mentioned themes, the study contributes to a deeper understanding of the complex and multifaceted nature of diasporic identity.